Empowering Arabic Educators in the Digital Era: Evaluating an AI-TPACK Professional Training Model - Mokhamad Azis Aji Abdilah; Subandji; Faizal Nur Abidin; Siti Aisyah; Esa Saputro; Fouad Larhzizer (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2026)
The digital competence of Arabic language teacher in Madrasah Tsanawiyah (MTs) in Sukoharjo remains low, particularly in developing interactive electronic student worksheets (E-LKPD). This study aims to test the effectiveness of AI-TPACK based training, integrating generative AI (ChatGPT and Teks To Speech) and Liveworksheets apps, in improving teacher competence. A quantitative approach with a quasi experimental one group design was employed. The sample consisted of 20 Arabic language teachers selected through purposive sampling from 11 different MTs. Data were collected using a validated questionnaire (Aiken’s V=0.87) and analyzed using Paired Sample T-Test and N-Gain scores. The results showed a significant increase across all competency variables (Sig. < 0.05), with an average N-Gain score of 0.59 (Moderately Effective). The highest increase occurred in AI-TPACK integration mastery (N-Gain = 0.76, Highly Effective). However, field implementation remains constrained by network infrascrtucture and device factors. These findings inply that the AI-TPACK training model is a strategic solution for developing teacher competence in the digital era.